Distribution System Operation Enhancement through Household Consumption Coordination in a Dynamic Pricing Environment - Paterakis, Nikolaos G.; Medeiros, Miguel F.; Catalao, Joao P. S.; Erdinc, Ozan (IEEE, 2015)
Increasing environmental concerns have motivated efforts for the modernization of the power system recently. As a result, the distribution system (DS) has been given specific importance. Especially, residential end-users have been rendered active trough the introduction of several assets such as electric vehicles, energy storage systems and self-production units. Although many opportunities emerge from the spreading of these so-called smart households, the DS may be negatively affected if appropriate coordination techniques are not developed. At this point, the distribution system operators (DSO) that are responsible for the operation of the DS need to intervene. The smart households struggle to minimize their daily electricity procurement cost by exploiting dynamic pricing tariff schemes. On the other hand, the DSO aims to minimize the active power losses of the DS. DS reconfiguration is a core element of the daily operational practice of DSO and should be considered in the development of coordination strategies. In this study, a two-side interaction framework is proposed in order to guarantee that both the smart households and the DSO sufficiently achieve their individual goals. State-of-the art computing techniques are also used in order to render the proposed formulation tractable for real-life applications.
Keywords: demand response; distribution system reconfiguration; grid computing; smart households; SMART GRIDS; ELECTRIC VEHICLES; LOSS REDUCTION; MANAGEMENT; Engineering